Soil Test Based Inorganic Fertilizer and Integrated Plant Nutrition System for Rice (Oryza sativa L.) Cultivation in Inceptisols of Bangladesh (The Agriculturists, 2016)
A field experiment was conducted at the Bangladesh Rice Research Institute, Gazipur during 2013 to study the potential of different organic materials in integrated plant nutrition system (IPNS) and soil test based (STB) inorganic fertilizer on the growth, nutrient uptake and yield of rice (Oryza sativa L.): variety BRRI dhan29. Five treatments were laid out in a randomized complete block design with four replications. The treatments were: (1) soil test based inorganic fertilizer (NPKS @ 138-7-80-3 kg ha-1), (2) cow dung (3 t ha-1), (3) poultry manure (2 t ha-1), (4) mustard oil cake (2 t ha-1) and (5) control. Organic fertilizers were applied on dry weight basis. Inorganic fertilizers were applied along with poultry manure (PM), cow dung (CD) and mustard oil cake (MOC) as IPNS. Soil test based STB fertilizer and PM in IPNS provided maximum grain yield of rice (6.11 t ha-1). Maximum plant height and tiller numbers were found in MOC treatment, while the numbers of filled grains were higher in STB fertilizer and PM treated plots. The application of different organic sources as IPNS significantly influenced the N, P, K and S uptake in rice. However, the highest N, P, K and S uptake were found in the PM treatment. The benefit cost ratio of different treatments followed the order of STB>PM>CD>Control>MOC. Considering yield potential and BCR, STB fertilizer and PM treatments were found economically profitable. However, from environmental point of view and sustainable management of soil health and crop productivity, application of PM and CD in rice-rice cropping system is recommended for rice cultivation.The Agriculturists 2016; 14(1) 33-42